3(a-6)=6a-(3a+18)

Simple and best practice solution for 3(a-6)=6a-(3a+18) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(a-6)=6a-(3a+18) equation:


Simplifying
3(a + -6) = 6a + -1(3a + 18)

Reorder the terms:
3(-6 + a) = 6a + -1(3a + 18)
(-6 * 3 + a * 3) = 6a + -1(3a + 18)
(-18 + 3a) = 6a + -1(3a + 18)

Reorder the terms:
-18 + 3a = 6a + -1(18 + 3a)
-18 + 3a = 6a + (18 * -1 + 3a * -1)
-18 + 3a = 6a + (-18 + -3a)

Reorder the terms:
-18 + 3a = -18 + 6a + -3a

Combine like terms: 6a + -3a = 3a
-18 + 3a = -18 + 3a

Add '18' to each side of the equation.
-18 + 18 + 3a = -18 + 18 + 3a

Combine like terms: -18 + 18 = 0
0 + 3a = -18 + 18 + 3a
3a = -18 + 18 + 3a

Combine like terms: -18 + 18 = 0
3a = 0 + 3a
3a = 3a

Add '-3a' to each side of the equation.
3a + -3a = 3a + -3a

Combine like terms: 3a + -3a = 0
0 = 3a + -3a

Combine like terms: 3a + -3a = 0
0 = 0

Solving
0 = 0

Couldn't find a variable to solve for.

This equation is an identity, all real numbers are solutions.

See similar equations:

| -23/24-19 | | 12.5x-20.25=98.5 | | -4x-23/6 | | 221-3x=33x+21 | | 8+8q=11+7q | | =log(x+4) | | 37=-3+5(x-6) | | -7x^6-14x^5+56x^4= | | 5-8x=130-43x | | f(x)=log(x+4) | | 2.4(-3/2^2-1/2) | | 27x^2-54x=0 | | 165=50+12(m) | | 5x+0.7=2.7 | | 4=2x+6+3x | | 6(-35/36)+2 | | 2x=12.4 | | 4x+(3x+40)=180 | | a^7+6a^6d-7a^5b^2= | | 3x=y+14 | | 4x+(3x+40)=90 | | -58-8x=10x+19 | | 5x+12=6x-10 | | 3x+10=82-62 | | a^5+6a^4b-7a^3b^2= | | 6-3(2w+4)=(8-w) | | 3x+1/2=5/6 | | (5x-9)/x=8y | | Qs=10+3p | | 8y=5x/x-9/x | | 2/9x100 | | 4a+2b=16 |

Equations solver categories